LuxR402 of Novosphingobium sp. HR1a regulates the correct configuration of cell envelopes - Segura, Ana; Molina, Lázaro (Frontiers in Microbiology, 2023)
Although there is some evidence to suggest that LuxR-solo proteins participate in inter-species or even inter-kingdom communication, most of the LuxR-solo protein functions are unknown. We have characterized the LuxR402 regulator of Novosphingobium sp. HR1a, a bacterial strain with the ability to establish high numbers in the plant rhizosphere and able to degrade a wide range of polycyclic aromatic hydrocarbons. LuxR402 controls the aggregation state of the bacterial culture; cultures of a mutant strain lacking this regulator flocculate in less than 3 h without agitation. We have demonstrated that the bacterial surface of the mutant is highly hydrophobic and that the mutant cells assimilate sugars slower than the wild-type. The flocculation mechanism has been demonstrated to be involved in the survival of the strain under unfavorable conditions; the luxR402 gene is repressed and produces flocculation in the presence of salicylate, a substrate that, although being assimilated by Novosphingobium, is toxic to cells at high concentrations. The flocculation of cultures in industrial setups has mainly been achieved through the addition of chemicals; these studies open up the possibility of controlling the flocculation by regulating the level of expression of the luxR402 gene.